Odwrót bohaterów. Śmierć syjonistycznego mitu Masady w fi lmie Twierdza Beaufort Josepha Cedara - Pietrzak, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Withdrawal of Heroes: Death of the Zionist Myth of Masada in Joseph Cedar’s Beaufort Masada is an ancient fortress, which during The First Jewish–Roman War (66–73 CE) served as a refuge for the last bastion of Jewish resistance. In the first half of the twentieth century, the history of the Masada’s defenders was absorbed by the Zionist movement and transformed into a vital national myth, which became an important element of the identity and culture of future Israelis. The main purpose of this article is to show the deconstruction of the Masada mythical narrative made by Israeli director Joseph Cedar in his movie Beaufort.